The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1097/ijg.0000000000001409
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness and Tolerance of Subliminal Subthreshold Transscleral Cyclophotocoagulation With a Duty Factor of 25% Versus 31.3% for Advanced Glaucoma

Abstract: Précis: Subliminal subthreshold transscleral cyclophotocoagulation (SS-TSCPC) with duty cycles 25% and 31.3% seems to be an effective approach to reduce intraocular pressure (IOP) in glaucoma that is refractory to medical management. Objective: The objective of this study was to compare the effectiveness and the tolerance of SS-TSCPC with a duty cycle of 25% versus 31.3% with Supra 810 nm Subliminal Quantel Medical laser stimulation for advanced glaucom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Forty per cent of eyes (4/10) in which UBM was performed showed a fine space between the sclera and the CB, suggesting an increased uveoscleral outflow (Benhatchi et al 2019). In another study, the same team has compared the efficacy and tolerance of the procedure using the same treatment durations (100 s per eye) and powers (2000 mW) but by comparing 2 groups of 20 eyes each according to a duty cycle of 25% or 31.3% (Keilani et al 2020). The surgical success rate 12 months after the first procedure (IOP between 6 and 21 mmHg or an IOP lowering by 20% from baseline with no increase in glaucoma medication from baseline) was higher in the group with a duty cycle of 31.3% (83.5%) than in the group with a duty cycle of 25% (65%).…”
Section: Mp‐tltmentioning
confidence: 99%
“…Forty per cent of eyes (4/10) in which UBM was performed showed a fine space between the sclera and the CB, suggesting an increased uveoscleral outflow (Benhatchi et al 2019). In another study, the same team has compared the efficacy and tolerance of the procedure using the same treatment durations (100 s per eye) and powers (2000 mW) but by comparing 2 groups of 20 eyes each according to a duty cycle of 25% or 31.3% (Keilani et al 2020). The surgical success rate 12 months after the first procedure (IOP between 6 and 21 mmHg or an IOP lowering by 20% from baseline with no increase in glaucoma medication from baseline) was higher in the group with a duty cycle of 31.3% (83.5%) than in the group with a duty cycle of 25% (65%).…”
Section: Mp‐tltmentioning
confidence: 99%
“…Keilani et al compared 25% duty cycle to 31.3% and found that the latter was more effective but induced more inflammation. 37 …”
Section: Introductionmentioning
confidence: 99%
“…The guidelines [ 24 , 27 ] provide a useful collection of evidence-based consensus mainly on the MicroPulse (IRIDEX) machine. On the other hand, data regarding the safety and the efficacy of the Supra 810 and Vitra 810 (Quantel Medical) machines are scarce [ 37 , 39 , 50 , 51 ]. Our results suggest that similar outcomes can be achieved with the Quantel machines, also broadening treatment options.…”
Section: Discussionmentioning
confidence: 99%
“…Review of the current literature shows that the criteria of success varies on a broad scale from IOP reduction of at least 20% [17,18,20,23,26,28,29,[33][34][35][36][37][38][39], IOP reduction of at least 30% [40][41][42][43], the variations of specific IOP and percentage limits [13,19,21,25,44], all the way to the most stringent criteria by Tekeli and Soussi [30,45]. In our study, the fulfilment of these criteria shows the discrepancy between the high proportion of patients with an IOP reduction of more than 30% (65%) versus the percentage of low target IOPs achieved (13%) with this method alone.…”
Section: Discussionmentioning
confidence: 99%